Academic Senate Minutes 2009-09-17 - Academic Senate:::::::::
Agenda approved. Minutes delayed. End of Year Reports received from the Senate, EPC, SAC, AAS and AFS. Update on WASC. APC Report. EPC Report. Provost Report. Vice President of SAEM Report. CFA Report. Associated Student Report. Chair-Elect Report. Resolution on Giving Priority to Reports – Failed. By-Laws Revision: Change to Charge of Structure and Functions – First Reading. FSAC Report. Resolution regarding Authority to Change SSU Teaching Schedule for Spring 2010 substituted, first reading waived and approved.